PENDIDIKAN INKLUSI DITENGAH KETERBATASAN: STUDI KASUS KESIAPAN GURU DAN SARANA PRASARANA DI SDN SUNGAI LULUT 7 - Arina Mawaddah Arina; Ahmad Syuriansyah; M. Syahman Rizani; Naila Azizah; Rahmadati; Wahdah Refia Rafianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
SDN Sungai Lulut 7 is one of the public primary schools designated to implement inclusive education, serving several students with special needs despite the absence of Special Education Teachers (GPK) and limited learning facilities. This study aims to describe teachers’ and school leaders’ understanding, instructional practices, and challenges in implementing inclusive education at the school. The research employed interviews, classroom observations, and document analysis. The findings indicate that both the principal and teachers demonstrate a positive conceptual understanding of inclusive education, particularly regarding student diversity and the need for instructional adjustments for learners with special needs. Teachers have attempted to apply differentiated instruction, visual learning materials, and individual guidance. However, inclusive practices remain at a basic level and face notable barriers, including the lack of GPK, limited resources, insufficient teacher competence in inclusive education, and minimal parental support. Strengthening teacher capacity, providing professional support staff, conducting formal assessments, and enhancing collaboration with families are essential to improving inclusive services.